The body in the gallery : a Faith Fairchild mystery - Page, Katherine Hall (Page, Katherine Hall. Faith Fairchild mystery., 2008)
Secretly assisting her museum president friend in a case involving a stolen piece of fine art, Faith Fairchild stumbles upon a murder scene near a controversial exhibit and becomes increasingly exasperated by the police's inability to recognize important clues.